P369 Should varicella vaccination be introduced into the national immunization guidelines?. (June 2019) - Nguyen, Emily; Baird, Olivia; Dzulkarnain, Mohamad; Wong, Krista; Ali-Bujang, Nazifa; Ooi, Siew-Ting; Kivlehan, Riona; Power, Ciaran; Molloy, Eleanor; Meehan, Judith
Abstract : Introduction: Varicella Zoster Virus (VZV) is a member of the herpesvirus family. The virus is transmitted via respiratory droplets and presents with fever and pruritic, erythematous vesicular skin lesions. Complications to VZV although uncommon, can be severe. The virus can remain dormant in sensory ganglia with potential to reactivate as Herpes Zoster. VZV can be prevented with a live attenuated vaccine derived from the Oka strain, given over two doses 4–8 weeks apart. Currently, the vaccine is given to high risk children (immunocompromised) in the Republic of Ireland or privately for the total cost of approximately €300. Objective: To determine if the VZV vaccine should be introduced as part of the Irish National Immunisation Guidelines. Secondary aims include examining vaccine cost-effectiveness, safety, comparisons to other vaccination programs and association with Herpes Zoster. Methods: A search was performed to identify articles on varicella vaccination published between 2008–2018 using the Pubmed database. Studies which focused on specific target groups such as immunocompromised individuals, the elderly, military population, irritable bowel disease, case studies, studies were excluded. Results: Our total search identified 642 papers of which 91 were used. Implementation in Other Countries: Countries adopting universal varicella vaccine programs have shown a reduction in the incidence of varicella cases and required hospitalizations due to varicella zoster-associated complications (US, Canada, Germany, Australia). The United States implemented the program in 1996 and demonstrated a decrease of up to 89% of varicella-related cases. Safety and Side Effects: Administration of 2-dose vaccine resulted in better immunity, with no serious adverse effects. Cellulitis, anaphylaxis and breakthrough infections have been reported post-vaccine. Cost-Effectiveness and Herpes Zoster Boosting: Implementation of the vaccine would be cost-effective if considering the impact on varicella in isolation. There is no evidence to suggest a link between the VZV vaccine and an increase in Herpes Zoster. Conclusion: Implementation of the varicella vaccine appears to be cost-effective if considering the impact on varicella in isolation.